Novel Orientations Innovation and Renovation in Mohsin Hamid’s “How to Get Filthy Rich in Rising Asia” - Hager Ben Driss (Glocalism: Journal of Culture, Politics and Innovation, 2019)
This article addresses Mohsin Hamid’s How to Get Filthy Rich in Rising Asia (2013). The narrative, which imitates a self-help or how-to guide, offers an intriguing textual terrain to engage questions of innovation and renovation. The writer uses a global model of writing, which enjoys high circulation and consumption, to engage in local concerns. Hamid’s novel provides a portrait of an entrepreneur as a young man. It engages in a diagnosis of Pakistan’s social and political maladies. I argue that Mohsin Hamid is particularly concerned in this novel with innovation on narratological and thematic levels. My investigation of the novel orientations in Hamid’s text attempts to press the borders of narratology to cultural territories. The narrative provides a pertinent example of the glocal, wherein literature becomes a site of dialogue and negotiation between the local and the global.